Stimulant use in sports - Jones, A. R.; Pichot, J. T. (American Journal on Addictions, 1998)
The authors provide an overview of the topic of stimulant use in psychiatric sports medicine. They address the following areas: 1) the history of stimulant use in sports; 2) recent events related to the use of stimulants in sports, including a new stimulant used at the 1996 Olympic competition in Atlanta, GA; 3) ergogenic or ergolytic (i.e., performance-impairing) potential of several major categories of stimulants, including amphetamines, beta2 agonists, caffeine, and cocaine; 4) review of how the brain reward circuit is affected by stimulants; 5) individual factors that induce athletes to utilize stimulants; and 6) sports organizational factors that induce athletes to use stimulants.